Assessment of myocardial fatty acid metabolic abnormalities in patients with idiopathic dilated cardiomyopathy using 123I BMIPP SPECT: correlation with clinicopathological findings and clinical course. Issue 2 (1st February 1999) - Yazaki, Y; Isobe, M; Takahashi, W; Kitabayashi, H; Nishiyama, O; Sekiguchi, M; Takemura, T
Abstract : Objective: To determine the clinical and prognostic value of identifying metabolic abnormalities of myocardial fatty acid metabolism in idiopathic dilated cardiomyopathy using iodine-123 β-methyl-iodophenyl pentadecanoic acid ( 123 I BMIPP). Setting: Cardiac care division in national hospital. Patients: 32 consecutive patients with idiopathic dilated cardiomyopathy in whom both 123 I BMIPP and thallium-201 myocardial single photon emission computed tomography were performed. Methods: The uptake of each tracer was scored visually from 0 (normal) to 3 (defect) in 17 segments (eight basal, eight midventricular, and one apical). A total score for all 17 segments was compared with clinicopathological variables. Prognostic value of mismatches between the two tracers were also evaluated. Results: The 123 I BMIPP total score was correlated with pulmonary capillary wedge pressure ( r = 0.68, p < 0.001), left ventricular end diastolic pressure ( r = 0.65, p < 0.001), percentage fractional shortening at six months' follow up ( r = -0.58, p = 0.001), myocyte diameter ( r = 0.66, p < 0.001), and percentage area of interstitial fibrosis ( r = 0.69, p < 0.001) measured by morphometry in the biopsy specimens. During a mean (SD) follow up of 20 (11) months, deterioration of the New York Heart Association functional class was observed in 11 of the 32 patients; four of these died. Segments with a greater decrease in 123 I BMIPP than thallium-201 uptake (type B mismatching) were often observed in patients with deterioration (88/187, 29% v 58/357, 16%; p < 0.001). Conclusions: The extent of the abnormality of myocardial fatty acid metabolism in idiopathic dilated cardiomyopathy reflects the severity of haemodynamic deterioration and histopathological changes. Type B mismatching is one of the important prognostic indicators in idiopathic dilated cardiomyopathy.